2013
DOI: 10.1590/s0001-37652013000300013
|View full text |Cite
|
Sign up to set email alerts
|

Germination responses of the invasive Calotropis procera (Ait.) R. Br. (Apocynaceae): comparisons with seeds from two ecosystems in northeastern Brazil

Abstract: Life history traits are considered key indicators of plant invasibility. Among them, the germination behavior of seeds is of major relevance because it is influenced by environmental factors of invaded ecosystem. Here, we investigated how seed traits and seed tolerance to environmental factors on seed germination of Calotropis procera vary depending on the invaded ecosystems in northeastern Brazil. We have tested seeds from two vegetation types -Caatinga and Restinga -to different levels of light intensity, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
4
11
0
1
Order By: Relevance
“…Different populations of the same species may have different germination behaviour when germinated under different environmental stresses, such as extreme temperatures, water availability and salinity (Leal et al , 2013; Meiado et al , 2016). These differences observed may be related to environmental characteristics where the parental plants produce their seeds (Baskin and Baskin, 2014; Contreras-Quiroz et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different populations of the same species may have different germination behaviour when germinated under different environmental stresses, such as extreme temperatures, water availability and salinity (Leal et al , 2013; Meiado et al , 2016). These differences observed may be related to environmental characteristics where the parental plants produce their seeds (Baskin and Baskin, 2014; Contreras-Quiroz et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Kappes, Andrade, Haga, Ferreira, and Arf (2010) observed that potentials above -0.3 MPa affect seed germination and vigor of Z. mays. Leal, Meiado, Lopes, and Leal (2013) found that saline stress negatively influenced the germinability of C. procera and completely inhibiting when the seeds were submitted to a concentration equal to or greater than -0.8 MPa.…”
Section: Physico-chemical Parametersmentioning
confidence: 98%
“…(Apocynaceae), Parkisonia aculeata L. (Fabaceae) e Prosopis juliflora (Sw.) DC. (Fabaceae) apresentaram tolerância à salinidade (Leal et al 2013). Bezerra et al (2013), trabalhando com a espécie invasora Parksonia aculeata, não verificaram interferência em sua germinação com o aumento da salinidade no substrato.…”
Section: Resultsunclassified